Parenting Patterns of Connected Parents in Developing Social Emotional Skills of Early Childhood - Nur Laela Hasanah; Dea, Leli Fertiliana; Azizah, Isnaini Nur (Bulletin of Early Childhood, 2024)
Parenting patterns greatly influence the social-emotional development of early childhood. In families with stepparents, differences in parenting approaches between biological parents and stepparents often cause imbalances, which can hinder children's growth and development. This study aims to examine the parenting patterns of stepparents in developing the social-emotional development of early childhood at RA Muslimat Baitul Huda Sidoharjo, Selagai Lingga, Central Lampung. This study uses a descriptive qualitative approach with a case study method, involving five stepparents and early childhood as research subjects. Data were collected through observation, in-depth interviews, and documentation, and tested for validity using triangulation of sources, techniques, and theories. The results of the study showed three tendencies of parenting patterns, namely positive, negative, and neutral. Positive parenting patterns are seen in the attitude of guiding, directing, and accompanying children in learning and socializing activities. Negative parenting patterns are characterized by the use of violence, minimal support, and lack of affection that makes children quiet and less confident. Neutral parenting occurs when children are given unlimited freedom or control, which makes children feel neglected. These three patterns influence children's social emotional development, depending on the consistency of implementation and existing communication.